The history of the Cape supreme court and its role in the development of judicial precedent for the period 1827-1910 - Fine, Hilton Basil (Centre for Law and Society, 2026)
Hahlo and Kahn have aptly described South African Law as a 'three-layered cake'. This dissertation is not so much concerned with the ingredients of the cake, but with the Cape Supreme Court which was used to 'bake' the third layer, and the judges who were employed to supervise the task. However, in order to wet the appetites of the legal gourmets, an attempt has been made to analyse the ingredient of judicial precedent, and to serve it up in the form of 'icing'. A survey of the traditional source materials utilized by lawyers, revealed a paucity of publications on the history of the Cape Supreme Court and on the early stages in the development of judicial precedent. It was therefore necessary to utilize archival material, government publications and unpublished theses. In approaching the subject, Hahlo and Kahn's concise survey proved to be an ideal starting point for conducting the investigation. Buttressed with Walker's biography of Lord de Villier's, 3 it was possible to obtain an overall picture of the developments which occurred during the period under consideration.